Purification and Characterization of Protease extracted from Bacillus licheniformis (B1) - Haider Jawad Kadhim; Sanaa Burhan Aldeen (Journal of Madenat Alelem University College, 2014)
Protease was purified by two steps included precipitation with 70% saturation ammonium sulphate and ion exchange chromatography by (DEAE-Sephadex). The enzyme specific activity was 86.6 U/mg. and fold of purification was 2.72 with 45 % enzyme recovery. Characterization of enzyme showed that the optimum pH for enzyme activity and stability was 9.0 (86 U/ml). Maximum enzyme activity appeared at 50°C. (88U/ml.). The enzyme activity remained was 87% at 50°C for 30 min. Effect of some metal ions, reducing agents and chelating on purified protease was studied, the remaining activity was 110% when it incubated with 10 mM of Mn2+, whereas the remaining activity was 95% and 92% when enzyme incubated with 10mM of Ca2+ and Mg2+, respectively. There was little effect for 10 mM of PMSF on enzyme activity, whereas the activity declined to 18% when enzyme was treated with 10 mM of 10 mM EDTA.